Oral Hygiene Awareness of Patients Undergoing Orthodontic Treatment - I Sinha; D Sinha (Islamic Azad University, 2023)
Background and Aim: Considering the significance of oral hygiene maintenance during orthodontic treatment, this study aimed to assess the oral hygiene awareness of patients undergoing orthodontic treatment and evaluate how compliant the patients are to the oral hygiene instructions given to them by dentists.    Materials and Methods:  Two researcher-designed questionnaires were used for assessment of oral hygiene awareness. One was given to patients between 12-40 years undergoing orthodontic treatment to assess the oral hygiene awareness of patients, and the other questionnaire was given to general dentists and orthodontists to assess their awareness regarding the provision of patients with ideal oral hygiene instructions. Each questionnaire consisted of 15 questions, and the study was conducted from June 2021 to August 2021. The questionnaires were administered online to 200 orthodontic patients and 200 dentists of various colleges in Tamil Nadu. Both male and female patients were included. The validity of the questionnaires was confirmed by a content validity index of 0.73. Results: Averagely 40% of patients did not follow the instructions given by their dentists and hence were unaware of oral hygiene maintenance measures during orthodontic treatment. The majority of patients (77%) were compliant to regular monthly appointments. Also, females were more concerned and more aware of how to maintain a good oral health, as compared to males. Conclusion: In the present study, most patients were compliant to their regular appointment schedules. A considerable number of patients did not follow the instructions given by their dentists and hence remained unaware of oral hygiene maintenance measures during orthodontic treatment.